A Narrative Review on the Role of Dalbavancin in the Treatment of Bone and Joint Infections - Dimitra Dimopoulou; Elpis Mantadakis; Christos Koutserimpas; George Samonis (Antibiotics, 2023)
Bone and joint infections (BJI) require prolonged antimicrobial treatment, leading to lengthy hospitalizations, high costs, the risk of nosocomial infections, and the development of antimicrobial resistance. Dalbavancin is a novel semisynthetic lipoglycopeptide approved for the treatment of adults and children with acute bacterial skin and skin structure infections. This narrative review aims to summarize the characteristics of dalbavancin and the current scientific evidence regarding its clinical efficacy and safety in the treatment of BJI. A literature search until June 2023 was performed to identify all published research about the role of dalbavancin in the management of BJI. Due to its unique pharmacokinetics characterized by prolonged half-life, high bactericidal activity against most Gram-positive bacteria, a good safety profile, and high tissue penetration, dalbavancin can be a valuable alternative to the treatment of BJI. Clinical studies have shown its non-inferiority compared to conventional therapies in BJI, offering potent activity against key pathogens and an extended dosing interval that may shorten hospitalization. In conclusion, dalbavancin represents a promising treatment option for BJI with a favorable safety profile, but further research in both adults and particularly children, who are ideal candidates for long-acting antibiotics, is necessary to evaluate the role of dalbavancin in BJI.